Analysis of scientific interpretations of tax control and inspections (Eurasian Research Bulletin, 2023)
In this article, research was carried out on ways to improve the activity of tax authorities and assess their efficiency in tax control in textile enterprises, and conclusions and proposals were formed within the framework of the research.